Managing conflict constructively - Tjosvold, Dean (Henry Stewart Talks, 2012)
Understanding conflict, Theory of cooperation and competition, Discussion for constructive conflict, Cooperative relationships, Chinese values on conflict management, Teams and organizations, Becoming conflict-positive